The conspirator [videorecording (DVD)] - Redford, Robert; Redford, Robert; Huston, Danny, 1962-; McAvoy, James, 1979-; Kline, Kevin; Wright, Robin, 1966-; Wood, Evan Rachel, 1987- (Lions Gate Home Entertainment, 2011)
Behind the story you've always heard about Abraham Lincoln's assassination, comes the thrilling true story about the people accused of conspiring to take down a government. In the wake of Abraham Lincoln's assassination, seven men and one woman are arrested and charged with conspiring to kill the President, Vice President, and Secretary of State. The lone woman charged, Mary Surratt, owns a boarding house where John Wilkes Booth, planned the simultaneous attacks.